Epítopos miméticos e autoantígenos aplicados ao imunodiagnóstico da artrite reumatoide e artrite idiopática Juvenil oligoarticular e poliarticular - Araujo, Galber Rodrigues (2015)
Introduction: Rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) are autoimmune rheumatic diseases of unknown cause characterized by inflammation, which can cause joint damage, and in some cases, damage to other parts of the body. To date, there is no single, definitive test for the diagnosis of RA and JIA, which is based on patient history, and various imaging and laboratory tests. In this context, the search for novel biomarkers with high sensitivity and specificity for RA and JIA is of great interest. Objectives: The aim of this study was to select, characterize and validate targets recognized by circulating antibodies that could be potentially described as autoantigens of RA or JIA. Methods: Phage Display technology was used to select peptides binding to circulating antibodies from mice presenting signs of arthritis after collagen type II induction (CIA model), and circulating antibodies from patients with JIA. In silico analysis, mass spectrometry and western blot were used to assist in the characterization of selected peptides. ELISA assays, ELISA avidity and differential pulse voltammetry was used as platform for detection of antibodies directed against the targets proposed in this study. Receiver Operating Characteristics (ROC) curve was determined for diagnostic accuracy for JIA and RA. Results: The M12 peptide selected against circulating IgGs from mice with signs of arthritis was able to discriminate RA patients from patients with other autoimmune diseases and healthy individuals (p < 0.0001) with high accuracy, presenting 91% specificity and 84.3% sensitivity. The M12 peptide was identified in an antigenic region of the protein carbonic anhydrase III, which has been previously identified as a RA autoantigen. The levels of antibodies to type II collagen were significantly higher in patients with JIA compared to levels obtained in patients with ankylosing spondylitis (p = 0.006) and healthy individuals (p < 0.0001). Moreover, the antibodies detection to type II collagen was more frequent in patients with ≤ 6 months duration (p = 0.0007). Antibodies displaying high avidity to collagen type II were associated with disease activity (p = 0.004). The PRF+1 peptide, selected from circulating IgGs from patients with JIA, was able to discriminate patients with JIA and RA from patients with other autoimmune diseases and healthy individuals (p < 0.0001) with high accuracy, presenting 91% specificity and 61% sensitivity for JIA, and 93% specificity and 94% sensitivity for RA. The electrochemical biosensor designed to detect antibodies against the peptide PFR+1 proved to be a fast, cheap and effective way of discriminating serum samples from patients with RA or JIA from healthy individuals. Conclusion: In a general analysis of the studies presented here, we conclude that the antigens used for the detection of circulating antibodies in patients with RA or JIA can be used with high accuracy to assist in diagnosis.